2018
DOI: 10.1007/s11126-018-9610-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Testing of Three Chinese Online-Related Addictive Behavior Instruments among Hong Kong University Students

Abstract: Objective: To validate the Chinese version of the nine-item Internet Gaming Disorder Scales-Short Form (IGDS-SF9), Bergen Social Media Addiction Scale (BSMAS), and Smartphone Application-Based Addiction Scale (SABAS) among Hong Kong university students. Participants and Methods: Participants aged between 17 and 30 years participated in the present study (n=307; 32.4% males; mean [SD] age=21.64 [8.11]). All the participants completed the IGDS-SF9, BSMAS, SABAS, and the Hospital Anxiety and Depression Scale (HAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
126
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(155 citation statements)
references
References 36 publications
26
126
2
1
Order By: Relevance
“…The psychometric properties of the SABAS and the Chinese SABAS have been found to be satisfactory. [20][21][22][23][24] The present study also showed that the Chinese SABAS had good internal consistency (α = 0.88).…”
Section: Smartphone Application-based Addiction Scale (Sabas)supporting
confidence: 72%
“…The psychometric properties of the SABAS and the Chinese SABAS have been found to be satisfactory. [20][21][22][23][24] The present study also showed that the Chinese SABAS had good internal consistency (α = 0.88).…”
Section: Smartphone Application-based Addiction Scale (Sabas)supporting
confidence: 72%
“…Fifth, our survey population was limited to students in a single prefecture in Japan; thus, it was a geographically limited population, so the results may lack generalizability. Finally, we did not investigate speci c Internet-use disorders [4,[63][64][65][66][67][68][69], which need to be studied in detail for preventive measures to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…A cut-off score over 19 indicates problematic social media use [51]. The BSMAS has satisfactory psychometric properties with high internal consistency (α = 0.819) and low floor and ceiling effects [34]. BSMAS scores correlated with IGDS9-SF scores and assessments of anxiety and depression [34].…”
Section: The Bergen Social Media Addiction Scale (Bsmas)mentioning
confidence: 99%
“…The current preliminary study was designed to explore how severities of IGD and SMA relate to sleep quality and emotional distress in a population at risk of internet addiction (i.e., young adults) [34] in order to complement prior studies of primary and secondary school students [1,35]. We hypothesized that both severities of IGD and SMA would relate to poorer sleep quality and more emotional distress.…”
Section: Introductionmentioning
confidence: 99%